PENGARUH PEMBERIAN BEBERAPA JENIS BAHAN ORGANIK TERHADAP STABILITAS AGREGAT TANAH ULTISOL LIMAU MANIS - Yulnafatmawita Yulnafatmawita; Adrinal Adrinal; Anita Febriani Daulay (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2008)
A field research about the effect of some sources of organic matter on aggregate stability of Ultisol was conducted in Limau Manis Padang. The research was aimed to investigate the contribution of different sources of organic matter to soil aggregate stability. Field research was arranged in Completely Randomized Block Design (RBD) consisting of 4 treatments (types of organic matter) and 3 replications (blocks). The treatments were : A = Tithonia diversifolia, B = Straw of Oryza sativa, C = Imperata cylindrica, and D = Leucaena glauca. The dosage for each treatment was 20 ton/ha based on dry weight. The result showed that Tithonia diversifolia gave the best contribution in improving soil aggregate stability of Ultisol Limau Manis for the first three (3) months.Keywords : organic matter, aggregate stability, marginal soil.